'Wave Elections', Charisma and Transformational Governance in India. (November 2019) - Rai, Praveen
After India's General Election of 2014, political analysts coined the term 'Modi wave' to depict the phenomenon of a strong leader who manages to obtain a major gain in a landslide victory. Still wondering whether this would be a one-off phenomenon, analysts found in 2019 to their surprise that India's most recent Parliamentary elections created a repeat wave. The article theorises the concept of 'wave election' and revisits earlier Indian elections to track the appearance of such waves. It then proceeds to examine what may make the most recent Modi 'wave' pertinent for future analysis, suggesting that more attention to the phenomenon of charisma and wider transformational agenda of governance rather than excessive focus on religion and saffron elements may be crucial to understand what is happening in India.